Reorientasi Pendidikan Nilai dalam Menyiapkan Kepeminpinan Masa Depan - F. Winarni F. Winarni (LPMPP Universitas Negeri Yogyakarta, 2006)
Advances in science the technology in general and thos related to transfer of informationa in particular have, besides positive effects, negative effects as well. Among the negative effects on society are moral and spiritual erosions in daily life. Education of values intended to be an effort to achieve the maintenance of an inner self sensitive to and filled with total comprehension of praiseworthy values has not been able to trnsfer the knowledge of values necessary for learners in dailing with the challenges facing them in their life to come. Success in education of values is especially important for the building of attitude and personality of prospective leaders.In orde to achieve deserable future leadership, it is necessary to establish in the profesional educatioan of leader candidates, especially in relation to their character building, some reorientation in their value education. Such reorientation can be in the form of, firs, enhancing the roles of the actors of education for all learners that will result in free dom in thinking, in being crative, in developing the imagination, and in materializing the values they believe to be good and true in thir life.